2015
DOI: 10.1016/j.jchf.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Terminal Pro-B-Type Natriuretic Peptide for Diagnosis and Prognosis in Patients With Renal Dysfunction

Abstract: Structured Abstract Objectives To determine if Amino-terminal Pro B-type Natriuretic Peptide (NT-proBNP) has different diagnostic and prognostic utility in patients with renal dysfunction. Background Patients with renal dysfunction have higher NT-proBNP, which may complicate interpretation for diagnosis of acute decompensated heart failure (ADHF) or prognosis. Methods We searched MEDLINE and EMBASE through August 2014 for studies with a subgroup analysis by renal function of the diagnostic or prognostic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 44 publications
4
47
0
4
Order By: Relevance
“…us, elevated levels of the prohormone are often observed in HD patients without clinical evidence of cardiovascular disease. ese high NT-proBNP levels in patients with renal dysfunction [11,12,[18][19][20] were higher than in individuals with normal renal function.…”
Section: Nt-probnp Levels In Hd Patientsmentioning
confidence: 82%
“…us, elevated levels of the prohormone are often observed in HD patients without clinical evidence of cardiovascular disease. ese high NT-proBNP levels in patients with renal dysfunction [11,12,[18][19][20] were higher than in individuals with normal renal function.…”
Section: Nt-probnp Levels In Hd Patientsmentioning
confidence: 82%
“…The use of NT-proBNP level in diagnosis has been recommended by guidelines for managing heart failure and acute coronary syndrome (ACS) in clinical practice [16,17]. However, several studies have found that blood NT-pro-BNP levels may be significantly affected by renal function [6]. This study found that NT-proBNP level is negatively correlated with eGFR in CAD patients, and the level is significantly elevated in patients with eGFRs of less than 60 mL/min/1.73 m 2 compared with patients with eGFRs of at least 90 mL/min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that for such patients, NT-proBNP level is significantly correlated with eGFR; in particular, NT-proBNP level increases as eGFR decreases [5,6]. Moreover, investigations have also revealed that the combined use of NT-proBNP level and eGFR can improve the identification of patients at high risk of acute myocardial infarction and heart failure [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, in the case of acute symptoms, a value of 300 pg/mL is thought to be abnormal. However, the increase of NT-proBNP concentration may occur in other conditions, including right ventricular overload, myocardial ischaemia, hypoxemia, renal dysfunction, liver cirrhosis, sepsis, and infection [9][10][11][12]. Even though NT-proBNP is increased in these conditions, it remains valuable in the HF diagnosis, but different cut-off values are suggested.…”
Section: Discussionmentioning
confidence: 99%